Investor protection and corporate governance : firm-level evidence across Latin America - Chong, Alberto; Lopez-de-Silanes, Florencio (Latin American development forum., 2007)
Investor Protection and Corporate Governance analyzes the impact of corporate governance on firm performance and valuation. Using unique datasets gathered at the firm-level - the first such data in the region - and results from a homogeneous corporate governance questionnaire, the book examines corporate governance characteristics, ownership structures, dividend policies, and performance measures. The book's analysis reveals the very high levels of ownership and voting rights concentrations and monolithic governance structures in the largest samples of Latin American companies up to now, and new data emphasize the importance of specific characteristics of the investor protection regimes in several Latin American countries. By and large, those firms with better governance measures across several dimensions are granted higher valuations and thus lower cost of capital.